Early Cinema Today, KINtop 1 : The Art of Programming and Live Performance - Loiperdinger, Martin (KINtop studies in early cinema, 2015)
Invented in the 1890s and premiered in Paris by the Lumiere brothers, the cinematograph along with Louis Le Prince's single-lens camera projector are considered by film historians to be the precursors to modern-day motion picture devices. These early movies were often shown in town halls, on fairgrounds, and in theaters, requiring special showmanship skills to effectively work the equipment and entertain onlookers. Within the last decade, film archives and film festivals have unearthed this lost art and have featured outstanding examples of the culture of early cinema reconfigured for today's audiences.